Table of contents, editorial board, and other front matter - Jim Shaner; Don Esslinger (Journal of Applied Communications, 1981)
Editorial front matter and table of contents for vol.64, no.2, April-June (1981) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education